Novel use of riociguat in infants with severe pulmonary arterial hypertension unable to wean from inhaled nitric oxide - Domingo, L. T.; Ivy, D. D.; Abman, S. H.; Grenolds, A. M.; MacLean, J. T.; Breaux, J. A.; Minford, K. J.; Frank, B. S. (Frontiers in Pediatrics, 2022)
Introduction: Riociguat, an oral soluble guanylate cyclase stimulator, has been approved for use in adults with pulmonary arterial hypertension (PAH) and chronic thromboembolic pulmonary hypertension. However, there is limited data on its therapeutic use in children. Case Presentation: We report the case of two infants with severe suprasystemic pulmonary hypertension who were successfully treated with riociguat after failure to wean off inhaled nitric oxide (iNO) despite combination PAH therapy. Case 1 is a 6-month-old term male with TBX4 deletion who presented with severe hypoxemic respiratory failure and severe PAH immediately after birth. Initial cardiac catheterization showed PVRi 15.5 WU*m2. Marked hypoxemia and PAH persisted despite aggressive therapy with sildenafil, bosentan, intravenous treprostinil, and milrinone. The baby required high doses of inhaled nitric oxide (60 ppm) and manifested significant post-ductal hypoxemia and hemodynamic instability with any attempt at weaning. After discontinuation of sildenafil, initiation, and very slow uptitration of riociguat the patient was able to maintain hemodynamic stability and wean from nitric oxide over 6 weeks with persistently severe but not worsened pulmonary hypertension. Case 2 is a 4-month-old term male with compound heterozygous SLC25A26 mutation and severe pulmonary hypertension. Initial cardiac catheterization showed PVRi 28.2 WU*m2. After of sildenafil, bosentan, and IV treprostinil serial echos continued to demonstrate near-systemic pulmonary hypertension. He failed multiple attempts to wean off typical doses of iNO (10-20 ppm) over the following weeks with tachypnea, hypoxemia, and worsening pulmonary hypertension on echocardiogram despite continued aggressive combination targeted therapy. After a 24-hour sildenafil washout he was initiated and up-titrated on riociguat with concomitant, successful wean of nitric oxide over one week that was well tolerated. No serious adverse effects in the titration period were observed. Conclusion: Riociguat may be considered as an adjuvant therapeutic agent in selected children with severe PAH who are poorly responsive to sildenafil therapy and unable to wean from iNO.